International consensus statements for endoscopic management of distal biliary stricture. Issue 6 (10th January 2020) - Nakai, Yousuke; Isayama, Hiroyuki; Wang, Hsiu‐Po; Rerknimitr, Rungsun; Khor, Christopher; Yasuda, Ichiro; Kogure, Hirofumi; Moon, Jong Ho; Lau, James; Lakhtakia, Sundeep; Ratanachu‐ek, Thawee; Seo, Dong Wan; et al.
Abstract: Distal biliary strictures (DBS) are common and may be caused by both malignant and benign pathologies. While endoscopic procedures play a major role in their management, a comprehensive review of the subject is still lacking. Our consensus statements were formulated by a group of expert Asian pancreatico‐biliary interventional endoscopists, following a proposal from the Digestive Endoscopy Society of Taiwan, the Thai Association for Gastrointestinal Endoscopy, and the Tokyo Conference of Asian Pancreato‐biliary Interventional Endoscopy. Based on a literature review utilizing Medline, Cochrane library, and Embase databases, a total of 19 consensus statements on DBS were made on diagnosis, endoscopic drainage, benign biliary stricture, malignant biliary stricture, and management of recurrent biliary obstruction and other complications. Our consensus statements provide comprehensive guidance for the endoscopic management of DBS.